Nutritional evaluation, phytochemical makeup, antibacterial and antioxidant properties of wild plants utilized as food by the Gaddis-a tribal tribe in the Western Himalayas - Thakur, Arti; Singh, Somvir; Dulta, Kanika; Singh, Nitesh; Ali, Baber; Hafeez, Aqsa; Vodnar, Dan C.; Marc, Romina Alina (Frontiers in Agronomy, 2022)
Nowadays it is generally accepted that medicinal plants play a crucial role in traditional healthcare operations, providing hints to new research fields and in biodiversity protection is now well recognized. However, there is a lack of information on the medicinal uses of plants in many of the Himalayan interior regions. In light of this, the current investigation was initiated in the tribally dominant western Himalayan hinterland.The current study examined five underutilised wild edible plants, including Allium rubellum, Berberis chitria, Berberis chitrium, Capsella bursa–pastoris, Stellaria aquatic and Rheum emodi for their nutritional qualities, phytochemical analysis, antioxidant activity, and antibacterial activity that are consumed as food by the Gaddi community of Bharmour region of District Chamba Himachal Pradesh. In thisstudy, the nutritional makeup of these plants was examined in terms of their carbohydrate, protein, sodium, potassium, crude fibre, and fat content. As compared to other investigated species, A. rubellum has the highest nutritional content such as carbohydrate (6.93mg/g), protein (10.18mg/g), sodium (3.21mg/g), potassium (16.32mg/g) and fibre (6.46%). In addition, phenols, amino acids, tannins, terpenoids, carotenoids, and phytate were found to be the least significant phytochemicals in R. emodi i.e. 4.81mg/g, 0.594mg/g, 2.204mg/g, 1.482mg/g, 156μg/g and 0.680%, respectively. Methanolic extract of these wild edible plants showed significant free radical scavenging activity by using ABTS and DPPH assay. Moreover, antibacterial activity of the methanolic extract of studied plants based on present study suggested that R. emodi exhibit maximum zone of inhibition 20.8mm against E. coli whereas S. aquatica showed maximum inhibition zone against S. aureus i.e.19.2mm.The findings of this study validated that these wild edibles plants are alternate source of medicine and are abundant source of various phytochemicals like protein, carbohydrates, vitamins, and minerals etc. These composition offer dietary benefits, food security, health benefits and therapeutic advantages. Hence, in the current study it was analyzed that there is an urgent need for documentation, conservation, characterization and evaluation of these underutilized plants for their therapeutic purpose and nutritional supplements.